Continuing Education for Teachers. Bibliographies in Education. No. 53 - Canadian Teachers' Federation, Ottawa (Ontario).; Canadian Teachers' Federation, Ottawa (Ontario). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This bibliography on continuing education for teachers covers a period of approximately five years, and is partially annotated. Some of the entries are available through ERIC and are listed with their ED numbers. The bibliography is divided according to the following subtopics: (1) competency-based programs; (2) continuing education in general; (3) the continuing education unit; (4) curriculum development by teachers; (5) delivery systems; (6) effects of inservice training on student learning; (7) inservice programs on behavior modification, environmental and outdoor education, family life, nutrition and consumer education, human relations, individualized instruction, language arts, reading, open classroom, physical education, science and mathematics, social studies, special education, and vocational and technical training; (8) leadership development; (9) planning and organizing inservice teacher education; (10) released time, course credits; (11) teacher centers; and (12) use of media inservice programs. (RC)
Availability: Canadian Teachers' Federation, 110 Argyle Avenue, Ottawa, Ontario, K2P 1B4 (No price quoted).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Competency Based Education; Credit Courses; Curriculum Development; Delivery Systems; Educational Media; Inservice Education; Inservice Teacher Education; Leadership Training; Released Time; Student Improvement; Teacher Centers; Reference Materials, Bibliographies